Menelusuri Konsep Filsafat Islam tentang Sejarah - Jaipuri Harahap (Aqlania, 2017)
Islamic philosophy is not only a study on theology, but also a study of way of life as a whole. Even though Greek Phylosophy regarded as a philosophical root, but it is not the one reference for Muslim Philosophers who try to absorp history as a consept. Greek and Islamic Philosophy have two different view -- if it is not contradictive -- on history.History in Islamic viewis to record on a part of God planning which is already appeared. It should be recognized that this world is existed because of God power, where everything is planned since azali time. Knowledge about history is a thing opened by God to the universe. From this point of view, history has influenced by religiousity. Thus, Islam adds morality in historical consept. Al-Quran, Muhammad, and all Muslims form the first generation had talked us about how important of a history. We all need to history. Therefore, study from the past and history should be placed as a guidance for the life in the future.